Optimalisasi Potensi Ekowisata Melalui Edukasi Bahaya Mikroplastik dan Inovasi Wine Jeruk di Desa Pengejaran - Lestari, Desak Putu Oki; Sudiarta, I Wayan; Sari, Ini Luh Putu Eka Kartika; Sukmadewi, Desak Ketut Tristiana (EDUPEDIA Publisher, 2025)
The Assisted Village Empowerment Program activities in Pengjaran Village, Kintamani, aim to optimize ecotourism through socializing the impact aof microplastics and innovation in processing oranges into wine. This village has enormous potential in the production of Siamese oranges but faces the challenges of overproduction and a lack of value-added processed products. This program involves training for Family Planning Program mothers regarding the dangers of microplastics and techniques for making orange wine, using outreach and hands-on methods. The results showed an increase in participants' knowledge about the impact of microplastics and their ability to produce orange wine. By reducing plastic use and promoting sustainable use of local resources, we hope to improve economic welfare and health in society. This program also supports the tourism industry by offering processed products that are attractive to tourists, thereby making a positive contribution to the local economy.